It's all about volatility of volatility: evidence from a two-factor stochastic volatility model - Stefano Grassi; Paolo Santucci de Magistris (University of Kent, School of Economics, 2013)
The persistent nature of equity volatility is investigated by means of a multi-factor stochastic volatility model with time varying parameters. The parameters are estimated by means of a sequential matching procedure which adopts as auxiliary model a time-varying generalization of the HAR model for the realized volatility series. It emerges that during the recent financial crisis the relative weight of the daily component dominates over the monthly term. The estimates of the two factor stochastic volatility model suggest that the change in the dynamic structure of the realized volatility during the financial crisis is due to the increase in the volatility of the persistent volatility term. A set of Monte Carlo simulations highlights th correctness of the methodology adopted to extract the variability in the parameters.
Keywords: G01; C00; C11; C58; 330; Time-Varying Parameters; On-line Kalman Filter; Simulation-based inference; Predictive Likelihood; Volatility Factors